KADAR GLIAL FIBRILLARY ACIDIC PROTEIN SERUM TINGGI SEBAGAI FAKTOR RISIKO NYERI NEUROPATIK PADA KUSTA TIPE MULTIBASILER - Sofyan Faridi; I Made Oka Adnyana; I Putu Eka Widyadharma; Luh Made Mas Rusyati (NEURONA, 2020)
Introduction : Leprosy is one of the most common causes of non-traumatic peripheral neuropathy in the world. There are many factors causing neuropathic pain in multibacillary (MB) type leprosy, one of which is an increase in serum levels of glial fibrillary acidic protein (GFAP). Aim: To prove high serum GFAP levels is a risk factor for neuropathic pain in MB type leprosy in Sanglah General Hospital Denpasar. Methods: This study was an observational analytic study with a case control design conducted at the Dermato-Venerology Department outpatient and in Pathological Clinic Laboratory in Sanglah General Hospital from November 2019 to January 2020. The sample of this study is all multibacillary leprosy patients with neuropathic pain who met inclusion criteria. A total of 60 patient were willing to participate in this study, the pain scales were measured using DN4 questionnaire and GFAP serum levels were examined. Chi-square test was performed to prove high serum GFAP levels is a risk factor of neuropathic pain in multibacillary leprosy. Results: High serum GFAP levels increase the incidence of neuropathic pain of MB type leprosy 5 times higher than controls (OR 5.72; p = 0.003), anxiety (OR 2.1; p = 0.24), and leprosy reaction (OR 2.2; p = 0.052). Discussion: High serum levels of GFAP is a risk factor of neuropathic pain in MB type leprosy in Sanglah General Hospital Denpasar. Keywords: GFAP, MB type leprosy, neuropathic pain